New Century (1999-2010) - Makarov, Andrey; Kolesnikov, Alexander (project baikal, 2015)
By the end of the millennium the primary accumulation of capital had become more restrained. Easy money still was in the air, but its amount had decreased. The circle of industrial magnates had been formed and strengthened. A large-scale redistribution of assets that resembled the civil war horrors became more civilized. The decade at the turn of the millennium was a watershed. It brought big changes into economy, politics and people’s way of life. We remember that decade as a period of subsiding fire, of pacific and relatively untroubled times. But also as times of lost opportunities, which were probably lost forever.
Keywords: watershed; Zodchestvo of Eastern Siberia; personal creative architectural bureaus